PEMUTUSAN HUBUNGAN KERJA SEPIHAK ANTARA PT. INECDA KEBUN SEBERIDA DENGAN TENAGA KERJA BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Nuraini Pane; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Termination of Employment for workers is a beginning of unemployment for workers with all its consequences. That's why the termination of employment often led to disputes between the companies with a workforce that industrial relations disputes. If the layoffs, the implementation must be in accordance with the provisions of the applicable law, the violation occurred at the PT. Inecda Gardens district Seberida Inhu, Rengat. Industrial disputes between workers and employers is due, the implementation of the termination of employment by the employer is not accompanied by the applicable law by conducting summary dismissal, the workers through the labor court, demanding that PT.Inecda rehire workers in the enterprise.Problem formulation in this research is how the mechanism of termination of employment between PT. Inecda with labor ?. Whether termination is incompatible with applicable laws ?. Is the legal remedy that can be done against arbitrary termination? The benefits of the berry research is the first to use theoretical benefit is as a support in pembendaharaan law science especially in employment law and as consideration for the next study, both practical benefits PT.Inecda as information and reference materials, labor better know their rights and responsibilities, and the public to know more information about the labor problems and.Based on the research results, it be concluded that termination of employment that do not comply with this PT.Inecda termination mechanisms that exist in the company's own rules and not in accordance with the provisions of Article 151 and Article 161 of Law Number 13 Year 2003 on Employment and also Act No. 2 of 2004 concerning Industrial Relations Dispute Resolution. Efforts made in the completion of termination of employment is subject to keputuan properly, which is in essence the termination of employment, termination of employment can not be done without the approval of a court settlement of industrial relations and without the consent of both parties. Thus settlement through the industrial relations court authorized to hear and give the verdict against industrial disputes.Keywords: RelationsEmployment Terminatio-Labor- PT.Inecda